Respon Pemberian Jenis Zpt Dan Lama Perendaman Yang Berbeda Terhadap Pertumbuhan Stek Batang Tanaman Anggur (Vitis vinifera L.) - Refa Firgiyanto; Isyrafil Arbi Juliantoro (Jurnal Penelitian Pertanian Terapan, 2022)
The formation of roots (adventive) and shoots as well as a slow dormancy period is an inhibiting factor for the successful implementation of cuttings. Increasing the slow growth of roots and shoots and accelerating plant dormancy is an effort to overcome this. The purpose of this study was to determine the growth response of grape stem cuttings (Vitis vinifera L.) to the immersion time on several types of PGR. This research was carried out for 3 months from January to April 2021 at the yard of Jurangsapi Village, Tapen District, Bondowoso Regency, East Java at an altitude of 226 meters above sea level. This study used a factorial randomized block design (RAK) with the first factor being the type of PGR (Z), with 3 levels, namely: Z1: Rootone-F 300 mg/liter of water, Z2: onion extract 800 ml/liter of water, Z3 : extract of bean sprouts 300 ml/liter of water, and the second factor is the long immersion (L) for 3 levels, namely: L1: 0.25 hours, L2: 6 hours, L3: 12 hours. The results showed that a single factor of PGR had an effect on increasing shoot length (8,10, and 12 WAP), shoot diameter (6 WAP), and number of leaves (10 and 12 WAP) of grape plants with the best PGR of Rootone-F. The long immersion treatment had a significant effect on the percentage of success in planting grape cuttings with the best soaking time of 6 hours. While the interaction between PGR type treatment and long immersion significantly affected shoot length (6,8,10, and 12 WAP), number of leaves (4, 8,10, and 12 WAP), and canopy wet weight of grape cuttings with the best treatment on PGR Rootone-F and 0.25 hours of long immersion. Keywords: auxins; long immersion; stem cuttings; Vitis vinifera L. var. prabu bestari.